Optimization of heat capacity measurement using DSC - Pilař, Radim; Honcová, Pavla; Košťál, Petr; Svoboda, Ladislav (University of Pardubice, 2013)
The methods of heat capacity data determination from DSC measurements were analysed and the negative effects increasing uncertainty of heat capacity were described. Optimization of stepwise method was done using molybdenum as a sample, and it leads to uncertainty of heat capacity up to 2 % in the temperature range from 288 to 823 K.